2020
DOI: 10.1634/theoncologist.2019-0680
|View full text |Cite
|
Sign up to set email alerts
|

Combined Expression of Plasma Thrombospondin-2 and CA19-9 for Diagnosis of Pancreatic Cancer and Distal Cholangiocarcinoma: A Proteome Approach

Abstract: Background. Minimally invasive diagnostic biomarkers for patients with pancreatic ductal adenocarcinoma (PDAC) and distal cholangiocarcinoma (dCCA) are warranted to facilitate accurate diagnosis. This study identified diagnostic plasma proteins based on proteomics of tumor secretome. Materials and Methods. Secretome of tumor and normal tissue was collected after resection of PDAC and dCCA. Differentially expressed proteins were measured by mass spectrometry. Selected candidate biomarkers and carbohydrate antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 43 publications
5
31
0
Order By: Relevance
“…( 40 )also revealed that THBS2 was significantly increased in pancreatic cancer tissues compared with normal tissues. In addition, both Kim ( 39 ) and Le Large ( 40 ) showed that the combined expression of THBS2 and CA19/9 in plasma can be used as a biomarker for PDAC patients. The above studies have shown that the overexpression of MMP14, ITGA2 and THBS2 promotes pancreatic cancer occurrence and development and indicate that they possess the ability to become therapeutic targets of PDAC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…( 40 )also revealed that THBS2 was significantly increased in pancreatic cancer tissues compared with normal tissues. In addition, both Kim ( 39 ) and Le Large ( 40 ) showed that the combined expression of THBS2 and CA19/9 in plasma can be used as a biomarker for PDAC patients. The above studies have shown that the overexpression of MMP14, ITGA2 and THBS2 promotes pancreatic cancer occurrence and development and indicate that they possess the ability to become therapeutic targets of PDAC.…”
Section: Discussionmentioning
confidence: 90%
“…Le Large et al ( 40)also revealed that THBS2 was significantly increased in pancreatic cancer tissues compared with normal tissues. In addition, both Kim (39) and Le Large (40) showed that the combined expression of THBS2 and CA19/9 in plasma can be used as a biomarker for PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…When utilized with CA19-9, it can boost detection of PC in high-risk populations which has been more recently affirmed[ 99 - 101 ]. Le Large et al [ 102 ] reported an AUC of 0.952 for THBS2 and CA19-9 in discriminating patients with cancer compared to healthy donors, however there was no difference in plasma THBS2 expression between patients with PC and distal cholangiocarcinoma highlighting a potential diagnostic dilemma and a lack of specificity associated with the assay[ 102 ].…”
Section: Serological Biomarkers Of Pcmentioning
confidence: 99%
“…These markers are also developing as prognostic/diagnostic factors in clinical study. Large et al demonstrated the co-expression of plasma thrombospondin-2 (THBS2) with CA19-9 in CCA patients [ 76 ]. Furthermore, MMP7, IL-6, S100A6, DKK1 and SSP411 are also abnormally expressed proteins in CCA patients’ serum [ 70 , 77 , 78 , 79 , 80 ].…”
Section: Protein Levels and Post-translational Modifications In CCmentioning
confidence: 99%